Revisão do gênero Farrimyia Dodge, 1965 (Diptera, Sarcophagidae), com base nos machos - Mello-Patiu, Cátia Antunes de (1991)
This dissertation is a taxonomic revision of the genus Farrimyia Dodge, 1965 (Diptera, Sarcophagidae), based on males. Farrimyia includes presently eleven known species, plus four F. bidentata (Dodge), F. ecitocola (Dodge), F. lenkoi (Lopes) and F. Metamassi (Lopes) transferred from Dekosarcophaga Townsend and herein proposed as new combinations. Fourteen species were redescribed and illustrated, only one F. megista (Hall) – was not available for study and its recent redescription was transcribed. Comments and informations on specific affinities, types and distribution are also given.